Velocity reserve as a mean to quantify the level of effort in resistance training. - Chéry, C. (Journal of Australian Strength and Conditioning, 2021)
The aim of the present article was to evaluate the strength and weaknesses of three velocity-based methods commonly used to quantify the level of effort during a lift, and to propose a new metric to regulate training volume. Thus far, the assessment of a degree of accumulated fatigue in a set is obtained through the use of percentages of velocity loss (%VL), individualized Exertion - Velocity (E-V) profile, or the effort index (EI). Although these methods are all based on the decrement of movement velocity during a lift, they do not possess the same relevance in regard to different efficiency criteria. Among these criteria, the understanding of the biofeedback, prescriptive convenience, and the possibility to transcribe positive, stable and negative trend in movement velocity needs to be considered. The concept of velocity reserve (?Vres) is based on a normalization of absolute %VL, according to a specific minimum velocity threshold achievable in a lift. This new metric allows for the quantification of a level of effort in relation to a maximal effort threshold corresponding to task failure, on a 0 to 100 scale. It therefore allows the standardization in the prescription of training volume, independently of the individual, the load, or the exercise considered. Practitioners aiming to target specific training adaptations should use %?Vres loss thresholds lower or equal to 15% to increase athletic related performances. Medium %?Vres loss, ranging from 15 to 30%, seems to be more efficient to improve strength. Finally, training for muscular hypertrophy requires achieving high %?Vres loss, equal or greater than 50%. On a theoretical plan, the %?Vres method constitutes a good alternative to quantify the level of effort during resistance exercise.